Allotransplantasi Testis Mencit Muda sebagai Upaya Preservasi Gonad In Vivo - Wahono Esthi Prasetyaningtyas; Kusdiantoro Mohamad; Mokhamad Fahrudin; Ita Djuwita; Srihadi Agungpriyono (Jurnal Ilmu Pertanian Indonesia, 2007)
Cancer disease are not detected only at adult but also at young age. One therapy for cancer diseases is chemotherapy and radiation, that give a side effect of infertility in the gonad, therefore, it is necessary to preserve the gonad. Sperm collection from adult is easy but not from the young patients.Keyword: transpalantation, testis, mencit muda, spermatogenesis